Analisis User Interface Website Garuda Indonesia Berdasarkan Prinsip Hick's Law - Liem, Vincent (Universitas Informatika dan Bisnis Indonesia, 2024)
Technological advancements have simplified life, particularly through websites that combine text, images, sound, and animation to attract visitors and disseminate information quickly. The design of User Interface (UI) and User Experience (UX) is crucial for the comfort and ease of website use. The Garuda Indonesia website facilitates the purchase and price checking of airline tickets, emphasizing user comfort to reduce human error, which can be minimized with adequate knowledge and motivation. This study uses Hick’s Law, which states that the more choices available, the longer it takes to make a decision, to analyze and recommend improvements for the Garuda Indonesia website to enhance its quality and functionality.